"The hand of a woman" Deborah and Yael (Judges 4) - ʿAsis, Eliyahu (2005)
This article focuses on the role of Yael in Judges 4. It argues that Yael's central position in the narrative is meant to shed light on Deborah's prophetic image. Yael is thus Deborah's “hand” – an extension of Deborah who carries out her prophecy: “for the Lord will deliver Sisera into the hand of a woman” (v. 9). Yael overshadows both Sisera and Barak. She controls both men; she decides who will be defeated and who will be victorious. Deborah's prophecy does not refer merely to the identity of the killer but also to the way in which the woman achieves her victory. Yael confronts a strong warrior, a general; physically she is inferior to him; she uses her femininity to defeat him. “While sexuality is a featured element of the Deborah narrative, it is so exclusively with reference to the actions of Yael. Deborah, the focus of the story, is, to be sure, a womanly figure. But her role in the story is purely that of a woman of God. It is she who reveals the hand of God in “the hand of a woman”.
Keywords: Deborah -- Biblische Person; Jael -- Biblische Person; Bibel